NONVERBAL COMMUNICATION BETWEEN THE VILLAGE HEAD AND PEOPLE WITH MENTALLY DISABLED IN KARANGPATIHAN VILLAGE PONOROGO - Nafiah, Siti Umi; Daroini, Muchlis (QAULAN: Journal of Islamic Communication, 2022)
Abstract: Communication is an important element in the life of society. In everyday, people communicate verbally using language or words, but not all humans are able to interact using only verbal communication. Humans who are less than perfect, such as people with mental disability, find it difficult to receive messages using only language. Mental disability is a mental and intellectual disability disorder below average. As in Karangpatihan Village, Balong District, Ponorogo Regency, where 98 residents are mentally disabled. The village head has an important role in the welfare of its citizens so that the use of signs, symbols and even simple facial expressions can help mentally disabled people more easily understand the ongoing communication. This research was conducted with a descriptive research method with a qualitative approach. Data collection techniques in the form of observation, interviews and documentation. Data analysis technique using Nonverbal Communication Theory according to Paul Ekman. The results of this study are first, the Village Head uses various signs/symbols when communicating with mentally disabled. Namely body language which includes eye gaze, facial expressions, hand gestures and movements, head movements, body posture and foot position, touch and paralanguage. Second, mental disability provides reciprocal responses in the form of nonverbal communication, namely, facial expressions, eye gaze, hand gestures and gestures and paralanguage. The gestures used are self-initiated without referring to sign language books in general.Keywords: Nonverbal Communication, Mental Disability, Paul Ekman's Theory.